Bilateral Total Hip and Unilateral Knee Arthroplasties in a Young Adult with Arthropathy-Associated Intestinal Epithelial Dysplasia (Tufting Enteropathy). (30th October 2018) - Ng, Colin; Magri, Kurt; Giordmaina, Ryan; Whitwell, Duncan
Abstract : Intestinal epithelial dysplasia (tufting enteropathy) is an uncommon congenital disorder. Furthermore, its association with chronic inflammatory arthropathy is rarely documented in the literature. Low prevalence rates of 1 in 100, 000 live births in Western Europe exist, with higher rates in North Africa and Middle Eastern countries. Malta, being a small Mediterranean island at the cusp between Europe and North Africa, has an anecdotal sevenfold prevalence rate. This is the first documented case report of a patient with both intestinal epithelial dysplasia and severe bilateral hip and knee arthropathy that required simultaneous bilateral hip followed by, after a short interval, unilateral knee arthroplasties. Our aim is to highlight the rapid progression of associated arthropathy as well as the successful treatment with joint arthroplasties in such extreme cases. Surgical treatment may be a necessity despite best medical efforts to halt the disease.